Fatigue Strength Evaluation Of Pressurizer Wall Structure In Pressurized Water Reactor - Himawan, Roziq (KnE Energy, 2016)
Fatigue strength evaluations have been performed to the pressurizer component in Pressurized Water Reactor. Fatigue is the main failure mechanism of material during system in operation. Therefore, this evaluation becomes important to be performed since the pressurizer has a very important function in the reactor’s system. Analysis was performed by using Nuclear Power Plant operation data from 40 years operation and base on Miner theory. This analysis covered all stress level experienced by the reactor during the service. To determine the value of fatigue usage factor a, fatigue curve of SA 533 material was applied. Analysis results show that the cumulative fatigue damage during 40 years in operation is 4,23×10-4. This value still far enough below failure criteria, which a value is 1. Therefore, the pressurizer design has already fulfilled the design qualification in term of fatigue aspect.